Pengaruh Pertumbuhan Ekonomi terhadap Pendapatan Nasional: Analisis Siklus Ekonomi, Faktor-Faktor Pendukung, dan Pertumbuhan Ekonomi di Tiongkok - rasuly, nasywa fiqa (Maliki Interdisciplinary Journal, 2025)
Economic growth is a key factor in the economy of a country, reflecting its ability to produce goods and services as well as serving as an indicator of societal well-being. This article analyzes the relationship between economic growth and national income through economic cycles, which consist of the phases of expansion, peak, contraction, and trough. These phases demonstrate different impacts on national income. China, as a case study, has shown how economic reforms since the late 1970s, export policies, and technological innovation have contributed to its rapid growth. By opening its market to foreign investment and emphasizing the importance of research and development, China has successfully increased its GDP and societal well-being. Understanding the supporting factors of economic growth is essential for policymakers to formulate effective strategies aimed at enhancing societal welfare sustainably.